SUGGESTIVE MODEL OF PHYSICAL EDUCATION IN NEP-2020 - Sharma, Seema; Lal, Rajender (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Education aims at all-round development, and the National Education Policy (NEP) 2020 emphasizes holistic education. It considers globalization and the transformation of education worldwide while remaining rooted in Indian culture, tradition, and values. Physical Education, a vital component of an integrated education system, educates the mind through movement and contributes to emotional, physical, and social well-being. This paper analyses NEP 2020 through the lens of Physical Education and proposes a stage-wise model suited to learners across different phases of life. From early childhood through lifelong learning, the model includes a variety of physical activities like movement education, sensory coordination, minor and major games, yoga, and dance. The paper also outlines academic domains for those pursuing Physical Education and sports sciences in higher education.